Intra-seasonal variability in supraglacial stream sediment on the Greenland Ice Sheet - Leidman, Sasha Z.; Rennermalm, Åsa K.; Muthyala, Rohi; Skiles, S. McKenzie; Getraer, Alexander (Frontiers in Earth Science, 2023)
On the surface of the Greenland Ice Sheet, the presence of low-albedo features greatly contributes to ablation zone meltwater production. Some of the lowest albedo features on the Ice Sheet are water-filled supraglacial stream channels, especially those with abundant deposits of consolidated cryoconite sediment. Because these sediments enhance melting by disproportionately lowering albedo, studying their spatial extent can provide a better understanding of Greenland’s contribution to global sea level rise. However, little is known about the spatial distribution of supraglacial stream sediment, or how it changes in response to seasonal flow regimes. Here, we surveyed a supraglacial stream network in Southwest Greenland, collecting imagery from seven uncrewed aerial vehicle (UAV) flights over the course of 24 days in 2019. Using Structure-from-Motion-generated orthomosaic imagery and digital elevation models (DEMs), we manually digitized the banks of the supraglacial stream channels, classified the sediment deposits, and modeled how the terrain influence the amount of incoming solar radiation at the Ice Sheet surface. We used classified imagery and in-situ spectrometer measurements to determine how changes in sediment cover altered albedo. We found that, within our study area, only 15% of cryoconite sediment was consolidated in cryoconite holes; the remaining 85% was located within supraglacial streams mostly concentrated to daily inundated riverbanks (hereafter termed floodplains). Sediment cover and stream width are highly correlated, suggesting that sediment influx into supraglacial drainage systems widens stream channels or darken previously widened channels. This reduces albedo in floodplains that already receive greater solar radiation due to their flatness. Additionally, the extent of stream sediments increased in August following seasonal peak flow, suggesting that as stream power decreases, more sediment accumulates in supraglacial channels. This negative feedback loop for melting may delay Greenland’s runoff to the latter end of the melt season. This study shows in unprecedented detail where and when sediment is deposited and how these deposits potentially impact the Ice Sheet surface energy balance. These findings may allow for better prediction of how supraglacial floodplains, and the microbiomes they contain, might change in response to increased melting.